2023
DOI: 10.1186/s40001-023-01379-x
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation parameters for the differential diagnosis of pancreatic cancer in the early stage: a retrospective study

Li Jiaao,
Ge Wanli,
Zhang Kai
et al.

Abstract: Background In recent years, conventional coagulation (CC) and thromboelastography (TEG) parameters have been reported to be closely related to the progression of pancreatic cancer (PC). However, the potential utility of these parameters in differentiating benign and malignant pancreatic diseases is still unclear. Objectives A retrospective study was conducted to evaluate the efficacy of coagulation parameters in differentiating pancreatic cancer/ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Furthermore, the abnormal coagulation parameters associated with PDAC have also brought to attention to the potential of using assorted coagulation parameters, in addition to US FDA approved serum cancer antigen CA19-9 marker, as a viable screening method for PDAC [ 4 ]. An elevated CA19-9 level was a significant risk factor for VTE and the occurrence of VTE was, overall, associated with poor prognosis in PDAC patients [ 80 ]. Another study showed that CA19-9 levels increase with the extent of VTE and are higher in PDAC patients with VTE compared to PDAC patients without VTE [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the abnormal coagulation parameters associated with PDAC have also brought to attention to the potential of using assorted coagulation parameters, in addition to US FDA approved serum cancer antigen CA19-9 marker, as a viable screening method for PDAC [ 4 ]. An elevated CA19-9 level was a significant risk factor for VTE and the occurrence of VTE was, overall, associated with poor prognosis in PDAC patients [ 80 ]. Another study showed that CA19-9 levels increase with the extent of VTE and are higher in PDAC patients with VTE compared to PDAC patients without VTE [ 81 ].…”
Section: Resultsmentioning
confidence: 99%